Influence of Psychographics and Risk Perception on Internet Banking Adoption: Current State of Affairs in Britain - Nasir, Muhammad Ali; Wu, Junjie; Yago, Milton; Li, Haohong (International Journal of Economics and Financial Issues, 2015)
This paper investigates the factors which determinate internet banking decisions among UK internet banking customers based on a survey which resulted into 191 usable questionnaire respondents randomly collected from a UK city. A Linear Regression technique is used to analyse data. It is found that perceived usefulness and perceived ease of use consistently have significant positive impacts on the decisions of internet banking adoption while these internet banking users are specifically concerned about security risk, privacy risk and financial risk related to using internet banking services. However, social risk has no significant impact on their decision to adopt internet banking. The findings indicate that traditional technology related factors are still relevant but psychological barriers, especially risk concerns have significant negative impacts on consumers’ attitudes towards internet banking. Keywords: Internet Banking; consumer perceptions; psychological barriers; UK. JEL Classifications: L81; L86; O33.